Efficacy of fertilizer on vegetative and reproductive traits of spring rice under System of Rice Intensification (SRI) - Niroula, Supriya (2025)
Rice is an important cereal crop and staple food of Nepal. The objective of this research was to identify the management of fertilizers that have relatively better performance and grain yield. Hence, a field study was conducted from February to July 2024 in the farmer’s field at Biratnagar, Nepal in a Randomized Complete Block Design (RCBD) with seven treatments: T1= Nitrogen as Urea, T2= Potassium as MOP, T3= Phosphorus as SSP, T4 = NPK, T5 = Farm Yard Manure, T6= Mustard Oilseed Cake, and T7= Control, each replicated thrice. Growth parameters and yield parameters data were recorded. The study revealed significant variations in growth and yield parameters across the different fertilizer treatments. The highest plant height (73.33 cm) at 45 days after transplanting was seen in T4, which also showed the highest grain yield (7.04 t.ha-1) and a significant number of effective tillers (29.43). The plots with NPK also had the highest number of tillers per unit area (21.03) whereas control had the lowest of 12.43. Conversely, the lowest grain yield (3.51 t.ha-1) was observed in control plots, which also recorded the lowest plant height (47.20 cm) and straw yield (3.97 t.ha-1). Incorporation of Farm Yard Manure and Mustard oilseed cake is strongly recommended along with NPK, as those treatments were also seen as excellent. If they are mixed with the NPK, the yield would potentially be increased as there would be positive interactions between them.